2017
DOI: 10.3126/njc.v1i1.25637
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma of Urinary Bladder presented as acute urine retention

Abstract: This report is of a 50-year-old man with a rare urinary bladder melanoma. He presented with hematuria followed by bladder outlet obstruction at the time of presentation. Ultrasonogram of the pelvis revealed a mass in the bladder outlet, suggestive of enlarged prostate. Suprapubic cystostomy was then performed. Subsequent transvesical exploration revealed a dark coloured mass at the outlet of bladder, which on histopathology confirmed to be melanoma. After ruling out other possible primary sites, he underwent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The symptoms caused by this tumor vary and depend on the location of the tumor 4 . The patient in our case complained of hematuria for one month.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms caused by this tumor vary and depend on the location of the tumor 4 . The patient in our case complained of hematuria for one month.…”
Section: Discussionmentioning
confidence: 99%
“…Gross hematuria is one of the most frequent presenting symptoms, and it also occurs in patients with bladder tumors, and may manifest differently depending on the size and location of the tumor in the bladder. It was reported that recurrent urinary tract infections could be an initial symptom in some patients with primary bladder melanoma 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms caused by this tumor vary and depend on its location [ 32 ]. The patient in our report complained of hematuria for 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that recurrent urinary tract infections, could be a presenting feature in some patients with PBM. 4 The initial diagnosis was made by the detection of the tumor on cystoscopy and by taking tissue samples with TUR. It is recommended to obtain samples and evaluate them for the presence of atypical melanocytes in the peritumoral bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%